Revealing the Barriers to Women's Political Participation in Uzbekistan - Alieva, Kamola (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
This article examines the structural barriers that continue to hinder women's political participation in Uzbekistan, focusing on socio-cultural, socio-economic, legal, and security-related challenges. Despite progress in education and employment, systemic discrimination, entrenched gender norms, and institutional constraints continue to limit women's access to political leadership and decision-making roles. This study explores the pathways to political representation and the extent to which women’s political agency is shaped by external pressures and internal institutional resistance. The article argues that while policy reforms and legal frameworks are necessary, they remain insufficient without broader institutional and societal transformation. It highlights that collective action, institutional support, and a sustained shift in public perception are crucial for breaking down the barriers to women’s political leadership. Drawing on qualitative research and survey data, the study underscores the intersection of legislative change, financial and mobility constraints, and gendered expectations, illustrating how these factors shape women's participation in governance. The research contributes to the discourse on political gender equity by examining how systemic forces interact with women’s leadership trajectories. It calls for a paradigm shift that extends beyond numerical representation toward meaningful political inclusion, ensuring that women not only enter political spaces but also exercise real influence in decision-making. [Artikel ini mengkaji hambatan-hambatan struktural yang terus menghalangi partisipasi politik perempuan di Uzbekistan, dengan fokus pada tantangan sosial-budaya, sosial-ekonomi, hukum, dan keamanan. Meskipun terdapat kemajuan di bidang pendidikan dan ketenagakerjaan, diskriminasi sistemik, norma gender yang mengakar, serta kendala kelembagaan tetap membatasi akses perempuan terhadap kepemimpinan politik dan peran pengambilan keputusan. Kajian ini menelusuri jalur menuju representasi politik serta sejauh mana agensi politik perempuan dibentuk oleh tekanan eksternal dan resistensi internal dari institusi. Artikel ini berpendapat bahwa meskipun reformasi kebijakan dan kerangka hukum diperlukan, keduanya masih belum memadai tanpa adanya transformasi kelembagaan dan sosial yang lebih luas. Penelitian ini menegaskan bahwa aksi kolektif, dukungan institusional, dan perubahan berkelanjutan dalam persepsi publik merupakan kunci untuk meruntuhkan hambatan terhadap kepemimpinan politik perempuan. Dengan menggunakan metode penelitian kualitatif dan data survei, kajian ini menyoroti keterkaitan antara perubahan legislatif, hambatan finansial dan mobilitas, serta ekspektasi berbasis gender, dan menunjukkan bagaimana faktor-faktor tersebut membentuk partisipasi perempuan dalam tata kelola pemerintahan. Penelitian ini berkontribusi pada diskursus kesetaraan gender dalam politik dengan mengkaji interaksi antara kekuatan-kekuatan sistemik dan perjalanan kepemimpinan perempuan. Artikel ini menyerukan perubahan paradigma yang melampaui representasi numerik menuju inklusi politik yang bermakna, sehingga perempuan tidak hanya memasuki ruang politik, tetapi juga memiliki pengaruh nyata dalam pengambilan keputusan.]